Case report: Severe dry cough associated with superior vena cava syndrome—Caused recurrent chylothorax - Wan, Ziming (Frontiers in Cardiovascular Medicine, 2022)
Introduction: Symptomatic pleural effusion is occasionally by superior vena cava syndrome. Dyspnea and pleuritic chest pain are common symptoms of pleural effusion. However, current literature has not reported severe dry cough as a symptom. Case Presentation: A patient with uremia suffered from unexplained severe dry cough, which could be triggered by postural changes. Medical examinations ruled out the possibilities of chronic bronchitis, gastroesophageal reflux, chest tumor, tuberculosis, asthma, chronic obstructive pulmonary disease, and allergy history. Examinations showed that the patient had chylous pleural effusion. The cough symptom was relieved after extraction of pleural effusion, but soon reappeared with the recurrence of chylothorax. Enhanced computed tomography showed that the patient had superior vena cava occlusion. After recanalization of the superior vena cava by percutaneous balloon dilatation, the patient no longer had chylothorax, and the severe cough was eliminated at the same time. Conclusion: Super vena cava syndrome can cause chylothorax and further stimulate severe dry cough. Cough is not a specific symptom. Chest imaging and pleural fluid analysis can help narrow down the diagnosis.